# prove the identity: 2cos^2 theta/2 = sin^2 theta/1-cos theta.

nick-teal | Certified Educator

calendarEducator since 2015

starTop subject is Math

Prove

`2cos^2(theta/2) = (sin^2theta)/(1-costheta)`

The half angle identity states:

`cos(theta/2) = sqrt((1+costheta)/2)`

This turns out left side into,

`2(1+costheta)/2 =(sin^2theta)/(1-costheta)`

`1+costheta =(sin^2theta)/(1-costheta)`

`(1-costheta)/(1-costheta) (1+costheta) =(sin^2theta)/(1-costheta)`

This simplifies into

`(1-cos^2theta)/(1-costheta) =(sin^2theta)/(1-costheta)`

Which turns into

`(sin^2theta)/(1-costheta) =(sin^2theta)/(1-costheta)`

It is proven!

check Approved by eNotes Editorial

Lupe Tanner, Ph.D. | Certified Educator

briefcaseCollege Professor

bookPh.D. from Oregon State University

calendarEducator since 2015

starTop subjects are Science, Math, and Business

Using the following identities:

`sin^2 x + cos^2 x =1`

and `cos^2 x = (1+cos 2x)/2`

Left hand side = 2 cos^2 (theta/2) = 2. (1+cos 2.theta/2)/2 = 1+cos theta

multiplying and dividing by (1-cos theta), we get.

LHS = (1+cos theta). (1-cos theta)/ (1-cos theta) = (1-cos^2 theta)/(1-cos theta)

= (sin^2 theta + cos^2 theta - cos theta)/(1cos theta) = sin^2 theta/ (1-cos theta). = RHS

Hence proved.

check Approved by eNotes Editorial

meaghan-vincent10121989 | Student

using half angle identities